Composition Operators on Some Banach Spaces of Harmonic Mappings. (19th February 2020) - Aljuaid, Munirah; Colonna, Flavia
Abstract : We study the composition operators on Banach spaces of harmonic mappings that extend several well-known Banach spaces of analytic functions on the open unit disk in the complex plane, including the α -Bloch spaces, the growth spaces, the Zygmund space, the analytic Besov spaces, and the space BMOA .